2020
DOI: 10.1002/lary.28773
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Orthonasal Olfaction and Chemosensory Perception in Patients With Smell Loss

Abstract: Objectives Self‐ratings seem to be the most effortless strategy for assessment of patients' chemical senses. Notably, although flavor perception strongly relies on olfaction, the relationship between self‐reported flavor perception and orthonasal olfactory tests have hitherto not been considered. The aim of this study was to investigate the relationship between self‐perceived olfactory function (SO), taste (ST), and flavor perception (SF) and smell test results in patients with olfactory dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…For this reason, it is important to conduct future studies using psychophysical olfactory assessments and gustometry, so as to establish the potential association between these sense disorders. About the positive association between subjective and psychophysical olfactory evaluations, our results supported those of previous study [19].…”
Section: Discussionsupporting
confidence: 92%
“…For this reason, it is important to conduct future studies using psychophysical olfactory assessments and gustometry, so as to establish the potential association between these sense disorders. About the positive association between subjective and psychophysical olfactory evaluations, our results supported those of previous study [19].…”
Section: Discussionsupporting
confidence: 92%
“…One explanation may be that the 7-CST is a screening test and thus, slight changes in olfactory function remained undetected. Another reason may be the poor correlation between subjective and tested olfactory function in general [41,42] and particular in COVID-19 patients [33]. However, significant differences between subjective function of smell and flavour before the onset of symptoms, on the first day of testing and after 7 weeks were observed.…”
Section: Discussionmentioning
confidence: 94%
“…However, there are few studies of the long-term evolution regarding OD and GD in COVID patients beyond the first weeks [ 4 , 17 ]. Likewise, no clear data is available on the association between OD and GD [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reported prevalence of gustatory dysfunction in COVID-19 infection is 43.93-56.4% [1,10]. Taste Dysfunction may also represent an early symptom suggestive of infection, but it remains unclear as to whether GD exists in COVID-19, or is a loss of retronasal smell [11]. This fact is due to the paucity of studies based on objective evidence for the measurement of GD since the reported prevalence of GD is mainly based on self-reported data [12].…”
Section: Introductionmentioning
confidence: 99%